Novel Wx alleles generated by base editing for improvement of rice grain quality. Issue 9 (19th May 2021) - Huang, Xiaorui; Su, Fei; Huang, Sheng; Mei, Fating; Niu, Xiaomu; Ma, Changle; Zhang, Hui; Zhu, Xiaoguo; Zhu, Jian‐Kang; Zhang, Jinshan
Abstract: Amylose content (AC), which is regulated by the Waxy ( Wx ) gene, is a major indicator of eating and cooking quality (ECQ) in rice ( Oryza sativa ). Thus far, only a limited number of mutations in the N‐terminal domain of Wx were found to have a major impact on the AC of rice grains and no mutations with such effects were reported for other regions of the Wx protein. Here, nucleotide substitutions in the middle region of Wx were generated by adenine and cytosine base editors. The nucleotide substitutions led to changes in 15 amino acid residues of Wx, and a series of novel Wx alleles with ACs of 0.3%–29.43% (wild type with AC of 19.87%) were obtained. Importantly, the waxy abe2 allele showed a "soft rice" AC, improved ECQ, favorable appearance, and no undesirable agronomic traits. The transgenes were removed from the waxy abe2 progeny, generating a promising breeding material for improving rice grain quality. Abstract : The waxy abe2 allele in the middle region of the Wx gene was generated by adenine and cytosine base editors. The mutants showed a "soft rice" amylose content, improved eating and cooking quality, favorable appearance, and no undesirable agronomic traits.